The Use Of Think Pair Share Technique In Writing Skill Descriptive Text For Grade Viii At Smp Negeri 1 Pematang Siantar - Jesana Tessalonika Simaremare (PT FORMOSA CENDEKIA GLOBAL, 2023)
The main objective of this study is to find out the effectiveness of students’ ability in writing descriptive text that taught by using Think-Pair-Share technique. This research was conducted at SMP Negeri 1 Pematang Siantar Academic Year 2022/2023. In this research, the population is students in the eighth grade. The numbers of population were 175 students. In taking the sample, Class VIII A and VIII B was chosen by using purposive sampling technique. There were 20 students in Class VIII A and 20 students in Class VIII B. The total samples were 40 students. Quasi-experimental method was applied in this research with two group pre-test and post-test design. Class VIII A was chosen as experimental class that taught by using Think-Pair-Share technique, and Class VIII B was chosen as control class that taught by using Conventional method. The instrument used to collect data was writing test. The result of the research showed that the eighth-grade students of SMP Negeri 1 Pematang Siantar had “fair” score on pre-test with the mean score 46.6. After giving treatment the students got improvement, the got “good” score with the mean score 84.05. The result of the data analysis indicated that there was a significant improvement in the students’ writing ability after being taught using Think-Pair Share technique. It was proved by the result of the statistical analysis of the level significance P = 0.05 with degree of freedom(df) = 38 indicated that the t-test values of the students’ writing (3.99) were higher than t- table value (2,021). Based on the result analysis, the researcher then concludes that the using Think-Pair-Share technique is effective to improve the students’ writing, especially in writing descriptive text and Think-Pair-Share technique was effective to improve students’ writing ability at the eighth-grade students of SMP Negeri 1 Pematang Siantar.